Uniform luminescent carbon nanodots prepared by rapid pyrolysis of organic precursors confined within nanoporous templating structures. (June 2017) - Ortega-Liebana, M.C.; Chung, N.X.; Limpens, R.; Gomez, L.; Hueso, J.L.; Santamaria, J.; Gregorkiewicz, T.
Abstract: Although several methods on the preparation of carbon nanodots (CNDs) emitting throughout the visible have been recently reported, in most of the processes the product suffers from inhomogeneity in size and shape limiting their impact. Here, we report the synthesis of undoped and nitrogen-doped luminescent carbon nanodots by rapid pyrolysis using ordered mesoporous silica nanorods as confining templates. A rapid thermal decomposition (pyrolysis) within the confined dimensions of their pores leads to a highly uniform size distribution of CNDs with average sizes below 4 nm. These CNDs are synthesized in an extremely short time period (5 min of reaction) by immersion in a fluidized-bed reactor that provides heating homogeneity and ensures fast heat transfer. In addition, a rapid release of the homogeneous CNDs can be easily achieved by a simple ultrasonication-filtration step that prevents further chemical action on the mesoporous templates. The emission of both undoped and N-doped CNDs in colloidal and solid state (with an efficiency of 1–5%) originates from a combination of quantum confinement effects and the presence of oxidized surface states; N-doping introduces resonant absorption states which participate in emission. Furthermore, we present a simple model to describe the excitation-dependent/-independent mechanism of carbon nanodots. Graphical abstract: